Development of Intron Polymorphism Markers and Their Association With Fatty Acid Component Variation in Oil Palm - Li, Jing; Yang, Yaodong; Sun, Xiwei; Liu, Rui; Xia, Wei; Shi, Peng; Zhou, Lixia; Wang, Yong; Wu, Yi; Lei, Xintao; Xiao, Yong (Frontiers in Plant Science, 2022)
Oil palm (Elaeis guineensis Jacq.) is a tropical woody oil crop of the palm family and is known as “the oil king of the world”, but its palm oil contains about 50% palmitic acid, which is considered unhealthy for humans. Intron polymorphisms (IP) are highly efficient and easily examined molecular markers located adjacent to exon regions of functional genes, thus may be associated with targeted trait variation. In order to speed up the breeding of oil palm fatty acid content, the current study identified a total of 310 introns located within 52 candidate genes involved in fatty acid biosynthesis in the oil palm genome. Based on the intron sequences, 205 primer pairs were designed, 64 of which showed polymorphism among 70 oil palm individuals. Phenotypic variation of fatty acid content in the 70 oil palm individuals was also investigated. Association analysis revealed that 13 IP markers were significantly associated with fatty acid content variation, and these IP markers were located on chromosomes 2, 5, 6, 8, 9, and 10 of oil palm. The development of such IP markers may be useful for the genetic improvement of fatty acid composition in oil palm.